Price transmission with error correction representation: an application to the South African Garlic Market - Mohale, Tumelo Arthur (My University, 2024)
There is a high demand for garlic both from the local and international markets. South Africa and the world as a whole have seen a sharp/significant increase in the consumption of garlic during the Corona Virus (COVID-19) era. South African garlic farmers are subjected to exploitation by middlemen such as retailers and wholesalers. This is usually exacerbated by the lack of market information presented to these farmers. This study attempted to test whether there is indeed price transmission in the South African garlic market or not. The aim of this study was to analyze price transmission in the South African garlic market. The study was conducted in South Africa. The objectives were to provide a description of farmgate, wholesale and retail prices in garlic markets; to determine correlation between farmgate, wholesale and retail prices; to determine the responsiveness of retailers towards a change in farmgate and wholesale garlic prices in South Africa; to determine the direction of price linkage between the farmgate, wholesale, and retail prices of garlic in South Africa and lastly, to determine price transmission in the South African garlic market. This study was conducted in South Africa following a quantitative approach. Secondary data on monthly garlic prices were sourced from the South African Department of Trade, Industry and Competition (DTIC); Joburg Market; National Agricultural Marketing Council (NAMC); and the South African Department of Agriculture, Land Reform, and Rural Development (DALRRD) covering the periods 2011 to 2021. Error Correction Model was used to analyze price transmission, preceded by Augmented Dickey-Fuller and Phillips-Perron tests for data stationarity. The Granger Causality test was also carried out. The study found the existence of Granger Causality in the South African garlic markets, with retailers responding quickly to price increases at farm and wholesale levels. The outcomes from Granger Causality test revealed a bidirectional price linkage between farmgate and wholesale prices, whereas there is a unidirectional linkage from the farmers and wholesalers to retailers. Through impulse response functions, the study found that retail prices respond faster to changes in wholesale prices than changes in farmgate prices. Additionally, variance decomposition revealed that wholesale prices are major determinants of retail prices in the South African garlic value chain. Through time series forecasting, the study found that farmgate, wholesale and retail prices in the South African garlic market are likely to continue fluctuating due to risks and uncertainties in the market. The study recommends that the government strengthens its efforts of regulating garlic markets, including other agricultural markets, in order to ensure a fair distribution of income along the marketing chain. It is further recommended that the government invests in the development of modern infrastructure and processing technology to enhance garlic production levels.
Thesis (M.Sc. (Agricultural Economics)) -- University of Limpopo, 2024
Keywords: Price transmission; Garlic markets; Error Correction model; Granger Causality tests; Co-integration; Variance decomposition; Impulse response functions; Value chain; Price regulation; Garlic industry; Produce trade; Agricultural economists